Resistência e complacência de pulmões descelularizados de camundongos através das técnicas de perfusão pela traqueia e artéria pulmonar - Urbano, Jessica Julioti (2016)
The actual scientific approach to bioengineering organs is based on the use of natural extracellular matrix of decellularized lung as initial departure for subsequent reconstruction of the organ for recellularization in a bioreactor. The decellularization technique can be performed by two infusion ways, one through the trachea and other by pulmonary artery. The aim of this studies was to investigate in an experimental animal model, by the occlusion at the end of inspiration (OEI) and movement equation (ME), the behavior of the elastic, viscous and viscoelastic mechanical properties, of mice lungs after the process of decellularization through the trachea and the pulmonary artery. Were used 30 male mice C57BL/6, weighing 17-18 g (7-8 weeks of age), anesthetized and euthanized by exsanguination through the abdominal aorta. The decellularization protocol comprised the following steps: collecting, cleaning, freezing and thawing, rinsing with sodium dodecyl sulfate and phosphate buffered saline. For the studies I and II, the lungs were divided into the control group (GC = 10), the decellularization group by the trachea (TDG = 10) and the pulmonary artery decellularization group (PDG = 10), 5 lungs in each group for the study I that had the analysis through the technique of OEI and 5 lungs in each group for the study II with analysis through the ME. In the study I, the values of static elastance (Eest = CG: 226.9 ± 4.1, PDG: 162.6 ± 3.9, TDG: 154.8 ± 1.7) and dynamics (Edyn = CG: 240 , 9 ± 6.7, PDG: 176 ± 5.4, TDG: 177.6 ± 1.6) were significantly lower in TDG and PDG when compared to CG. In study II, the value of lung resistance presented in TDG was significantly lower in relation to the other two groups (R = CG: 5.32 ± 0.26; PDG: 5.94 ± 0.24; TDG: 2.85 ± 0.14) and GC elastance was significantly higher in comparison with TDG and PDG, and in PDG the difference was significantly lower in relation to TDG (E = CG: 279 ± 13.81; PDG: 146 ± 19.04, TDG: 209.6 ± 12.06). We can observe in both the two-way decellularization are effective to provide a scaffold ideal for pulmonary later recellularization when evaluated by the OEI and ME. Furthermore, the decellularized lungs through the pulmonary artery may be used to create a pulmonary scaffold in less time, because the protocol can be performed in a day, which facilitates the process for obtaining functional lungs scaffolds.